2022
DOI: 10.1038/s41467-022-29085-y
|View full text |Cite
|
Sign up to set email alerts
|

A non-dividing cell population with high pyruvate dehydrogenase kinase activity regulates metabolic heterogeneity and tumorigenesis in the intestine

Abstract: Although reprogramming of cellular metabolism is a hallmark of cancer, little is known about how metabolic reprogramming contributes to early stages of transformation. Here, we show that the histone deacetylase SIRT6 regulates tumor initiation during intestinal cancer by controlling glucose metabolism. Loss of SIRT6 results in an increase in the number of intestinal stem cells (ISCs), which translates into enhanced tumor initiating potential in APCmin mice. By tracking down the connection between glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…We and others have revealed SETD2 deficiency-caused metabolic reprogramming 27,32,46 47,48 and our current study identified several metabolic pathway changes in SETD2 deficiency-caused ccRCC via transcriptomics and proteomics, emphasizing the utility of multi-omics dataset. Tumor suppressors-deficiency are known to alter metabolic pathways to promote the proliferation of tumor cells and tumor metastasis 15,[49][50][51][52] . Furthermore, changes in cell metabolism caused by tumor suppressors-deficiency are mostly glucose transport, glycolysis, amino acid metabolism, tricarboxylic acid cycle, fatty acid biosynthesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have revealed SETD2 deficiency-caused metabolic reprogramming 27,32,46 47,48 and our current study identified several metabolic pathway changes in SETD2 deficiency-caused ccRCC via transcriptomics and proteomics, emphasizing the utility of multi-omics dataset. Tumor suppressors-deficiency are known to alter metabolic pathways to promote the proliferation of tumor cells and tumor metastasis 15,[49][50][51][52] . Furthermore, changes in cell metabolism caused by tumor suppressors-deficiency are mostly glucose transport, glycolysis, amino acid metabolism, tricarboxylic acid cycle, fatty acid biosynthesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lactate may be a fuel used by cells of lung cancer, and that radiolabeled lactate infused to patients results in incorporation of the radioactive label in TAC intermediates [6]. A very recent article shows that the Warburg effect is important in non-dividing intestinal cells, not for energy but to combat oxidative stress [7]. There is convergent evidence pointing to TAC as instrumental in cancer; there is for instance the observation that tumorigenesis is limited when mitochondrial DNA is removed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that PKM2 has a pivotal role in cancer cell bioenergetics, ultimately governing the Warburg effect, i.e., the high glucose consumption and lactate production that most cancer cells display even in the presence of adequate oxygen concentrations and intact cellular machinery devoted to mitochondrial ATP production (16,22,23,30). Warburg effect is also essential for protecting cancer stem cells from their elevated ROS production (31).…”
Section: Discussionmentioning
confidence: 78%